High Performance Metal Oxide–Graphene Hybrid Nanomaterials Synthesized via Opposite‐Polarity Electrosprays. Issue 46 (6th October 2016) - Tang, Justin; Liu, Wen; Wang, Hailiang; Gomez, Alessandro
Abstract : An opposite‐polarity electrospray technique is developed to synthesize Mn3 O4 –graphene hybrid nanomaterial that shows high specific capacity, fast charging/discharging capability, and long cycle life for lithium storage. The approach offers nanoparticle size control and tunability, morphology control, versatility for the synthesis of different materials and hybrid structures from different precursors, and continuous‐flow nanomanufacturing with the potential for full automation.